Urate promotes SNCA/α-synuclein clearance via regulating mTOR-dependent macroautophagy - Sheng, Yu-Lan; Chen, Xing; Hou, Xiao-Ou; Yuan, Xin; Yuan, Bao-Shi; Yuan, Yu-Qing; Zhang, Qi-Lin; Cao, Xian; Liu, Chun-Feng; Luo, Wei-Feng; Hu, Li-Fang (Experimental neurology, 2017)
Serum urate levels are reported to be significantly lowered in patients with Parkinson's disease (PD) and inversely correlated to the risk and progression of PD. However, the mechanism by which urate affects PD is poorly understood. Here we showed that treatment with uric acid (UA) resulted in an autophagy activity enhancement in PC12 cells in dose- and time-dependent manners, as indicated by LC3-II increase and P62 decrease. Moreover, UA was still able to increase the LC3-II level and the number of LC3 puncta in the presence of Bafilomycin A1, a lysosomal inhibitor. These changes of autophagic markers were preceded by mTOR inhibition and ULK1 activation. Co-treatment with 3-benzyl-5-((2-nitrophenoxy) methyl)-dihydrofuran-2(3H)-one (3BDO), an mTOR activator, abolished the UA-induced LC3-II increase. More importantly, UA reduced SNCA/α-synuclein accumulation in PC12 cells that overexpress wildtype or A53T mutant SNCA, and this was blocked by Bafilomycin A1 co-treatment. The in vivo study showed that UA administration was able to modulate the levels of autophagy markers, increase the autophagosome/autolysosome formation, and reduce SNCA accumulation in the midbrain of SNCAA53T transgenic mice. Taken together, our findings suggest that UA could induce autophagy activation via an mTOR-dependent signaling and ameliorate SNCA accumulation. This implicates that urate-elevating agent may become a potential strategy for PD therapy. •Uric acid enhances macroautophagy activity in dopaminergic cells.•Uric acid induces autophagy activation dependent on mTOR inhibition.•Uric acid promotes α-synuclein degradation via the autophagy-lysosome pathway.•Uric acid treatment reduces α-synuclein accumulation in SNCAA53T transgenic mice.